2010
DOI: 10.1111/j.1742-4658.2010.07920.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of matrix metalloproteinase activity in health and disease

Abstract: The activity of matrix metalloproteinases (MMPs) is regulated at several levels, including enzyme activation, inhibition, complex formation and compartmentalization. Regulation at the transcriptional level is also important, although this is not a subject of the present minireview. Most MMPs are secreted and have their function in the extracellular environment. This is also the case for the membrane‐type MMPs (MT‐MMPs). MMPs are also found inside cells, both in the nucleus, cytosol and organelles. The role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
297
1
14

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(321 citation statements)
references
References 150 publications
5
297
1
14
Order By: Relevance
“…In the first case, it promotes the proliferation of neoplastic cells and metastatic dissemination through the degradation of the extracellular matrix and basal membrane, while indirectly it promotes angiogenesis, providing nutrition and dissemination of the tumor. 14 The first evidence of the involvement of MMPs in cancer came from studies in animal models. Experiments with tumor cells in mice showed that benign tumor cells acquire malignant properties when there is increased expression of these enzymes.…”
Section: Zinc and Metalloproteinases Of The Extracellular Matrixmentioning
confidence: 99%
“…In the first case, it promotes the proliferation of neoplastic cells and metastatic dissemination through the degradation of the extracellular matrix and basal membrane, while indirectly it promotes angiogenesis, providing nutrition and dissemination of the tumor. 14 The first evidence of the involvement of MMPs in cancer came from studies in animal models. Experiments with tumor cells in mice showed that benign tumor cells acquire malignant properties when there is increased expression of these enzymes.…”
Section: Zinc and Metalloproteinases Of The Extracellular Matrixmentioning
confidence: 99%
“…According to Kojima, Hoso, Watanabe, Matsuzaki, Hibino, Sasaki 46 , these changes may be related to the presence of flocculation, corrosion and cracks in the articular cartilage. Taking into consideration the findings of studies by Hadler-Olsen, Fadnes, Sylte, Uhlin-Hansen, Winberg 47 and Takaishi, Kimura, Dalah, Okada, D'Armiento 48 , the changes that were observed in the present study in the LG and EG may have been the result of an increase in the rate of synthesis and the secretion of matrix-degrading enzymes by chondrocytes, as well as the production of metalloproteases that are capable of unfolding collagen and proteoglycans, which release their fragments in the articular fluid, thereby weakening the cartilage matrix. Synovial fluid and the fibrous articular capsule respond to these fragments and other biochemical mediators, such as cytokines and leukotrienes, which leads to changes in the other components of the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Они запускают гидролиз фибриллярных коллагенов, которые составляют основу соединительнотканного барьера при развитии деструктивных инвазивных процессов, а также участвуют в гидролизе коллагена базальных мембран (через ММП-2), способствуя метастазированию [40][41][42]. В настоящее время у человека известно шесть МТ-ММП [37,43]. Наиболее изученной является МТ1-ММП (рис.…”
Section: фурин как фактор запускающий каскад реакций связанных с аunclassified
“…Однако этот фермент непосредственно не гидролизует коллаген IV типа, основу базальных мембран, но он активирует проММП-2, которая гидролизует коллаген IV типа и обеспечивает развитие метастатического процесса [44][45][46]. МТ1-ММП отвечает за активацию и проММП-13 (коллагеназы 3), которая обладает широкой субстратной специфичностью, гидролизует фибриллярные коллагены, коллаген IV типа и целый ряд компонентов СТМ, принимает участие в развитии онкологических поцессов [43,46,47]. Механизм активации этого фермента неизвестен [24].…”
Section: фурин как фактор запускающий каскад реакций связанных с аunclassified